High contiguity Arabidopsis thaliana genome assembly with a single nanopore flow cell - Todd P. Michael (Nature Portfolio, 2018)
Long-read sequencing technologies facilitate efficient and high quality genome assembly. Here Michael et al. achieve a fast reference assembly for Arabidopsis thaliana KBS-Mac-74 accession using the handheld Oxford Nanopore MinION sequencer and consumer computing hardware, and demonstrate its usefulness in resolving complex structural variation.